Tinjauan Durabilitas Campuran Asphalt Concrete Wearing Course Menggunakan Aspal Tua Dengan Berbagai Bahan Peremaja - Ratna Yuniarti; Desi Widianty; Rohani Rohani; Hasyim Hasyim (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
Asphalt concrete wearing course is laid on the top of road pavement so that directly exposed to ultra violet light and other environment impact. The higher temperature at the pavement surface and exposure to atmospheric oxygen accelerated aging cause asphalt to stiffen and become brittle. This aging result decrease the binding of asphalt and aggregate leads various damage of pavement. The aged asphalt rejuvenated and recycled with rejuvenating agent has been developed to reduce the use of virgin material for road maintenance. This article aims to review durability of asphalt concrete wearing course using waste cooking oil, epoxy resin, kerosene and waste engine oil as asphalt rejuvenators. Aging asphalt was prepared by heating in an oven at 85 oC for 120 hours (long term oven aging). Durability was assessed from the value of Marshall immersion which represent the resistance of asphalt mixture at water immersion. Relation between Marshall immersion and voids in mix (VIM), voids in the mineral aggregate (VMA), voids filled with bitumen (VFB) and density are also evaluated. From the analysis, it can be concluded that the use of waste cooking oil, epoxy resin, kerosene and waste engine oil as asphalt rejuvenators increase the durability of asphalt mixture containing the aged asphalt.